2004
DOI: 10.1093/ilar.45.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Therapies and Osteoporosis

Abstract: Osteoporosis, now defined as a disease characterized by low bone mass and a microarchitectural deterioration of bone tissue leading to enhanced bone fragility and fracture risk, is a major public health problem. Classic hormonal therapies to prevent and treat osteoporosis associated with menopause have recently been questioned due to the risk/benefit ratio of prolonged treatment. There is a critical need for safe and effective alternative therapeutics for this disease. Nonhuman primates have been used as model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…While this work has been helpful in understanding some of the biological factors that contribute to healthy aging, rodent models are limited by several key characteristics that make them dissimilar to primates and unsuitable for study of the association of physical mobility with risk of many diseases. For example, unlike primates, rodents continue to grow slowly throughout life and their skeletal metabolism differs from that of primates (Jerome 2004). Old World monkeys (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While this work has been helpful in understanding some of the biological factors that contribute to healthy aging, rodent models are limited by several key characteristics that make them dissimilar to primates and unsuitable for study of the association of physical mobility with risk of many diseases. For example, unlike primates, rodents continue to grow slowly throughout life and their skeletal metabolism differs from that of primates (Jerome 2004). Old World monkeys (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of ovarian function may cause a 30% decrease of skeletal mass in women after menopause, due to their bone resorption increase and imbalance between the amounts of resorbed and formed bone at each remodeling site [10,11]. Bone loss in OVX animals is similar to that in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased bone mass and bone turnover after menopause in macaques occur to a similar degree as in humans, and 1 year after surgical menopause, macaques experience a level of bone loss comparable to bone loss 3-4 years after natural menopause in women. [22][23][24][25] The findings of comparative research have reported that drug trials using macaque models agree with data available from drug trials in women. 23,26 Macaque models, therefore, are useful in studying bone health because they allow for bone measurements difficult to obtain in women.…”
Section: Introductionmentioning
confidence: 58%
“…However, cynomolgus monkeys are a well-documented model in which to study these findings. [22][23][24][25][26] Using human models, it is nearly impossible to recreate the tightly controlled environment achieved in this cohort. As we do not know the ideal 25OHD 3 concentrations for optimum health in humans or monkeys, we analyzed the data based on the relationships between higher vs. lower 25OHD 3 concentrations as surrogates for adequate vs. inadequate.…”
Section: Discussionmentioning
confidence: 99%